Study on consumers' motivation to buy green food based on meta-analysis - Cheng, Ling; Cui, Haiyang; Zhang, Zhiyong; Yang, Mingwei; Zhou, Yingling (Frontiers in Sustainable Food Systems, 2024)
Introduction There exists a noticeable gap between consumers' willingness to purchase green food and their actual purchase behavior. However, the awareness of green development is a crucial factor influencing this purchase behavior and acts as an internal driving force promoting green consumption. Consumers' green development awareness is shaped by various psychological motivations, including environmental concern, health consciousness, knowledge, norms, and price considerations. The existing literature often focuses on specific regions or groups, lacking comprehensive cross-regional and multivariate evaluations, and frequently overlooks the potential impact of moderating variables such as economic development level, product type, and behavior type. Methods To clarify the overall effect of each motivational factor on green food purchase behavior, this study conducted a meta-analysis. We selected eight causal variables and three moderating variables that significantly influence consumers' green food purchase behavior. The analysis included 132 independent effect values from 45 research papers. Results The meta-analysis revealed that: Consumers' green food purchase behavior is significantly positively correlated with eight motivational factors: environmental awareness, health awareness, green attitude, green knowledge, subjective norms, price awareness, perceived behavior control, and perceived usefulness. Economic development level, product type, and behavior type significantly affect consumers' green food purchase behavior. The impact of motivational factors on actual purchase behavior is weaker than on purchase intention, suggesting that interventions should focus on converting purchase intentions into actual purchase behavior. The findings indicate that environmental responsibility, government policies, and marketing strategies can influence consumers' psychological motives, guiding them toward more responsible consumption choices. Discussion Enhancing consumers' environmental and health awareness is essential, and policy support and marketing strategies can effectively promote green food consumption. These insights underscore the importance of targeted interventions to bridge the gap between green purchase intention and behavior.